2016
DOI: 10.1007/978-3-319-28802-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Psyche, Signals and Systems

Abstract: For a century or so, the multidisciplinary nature of neuroscience has left the field fractured into distinct areas of research. In particular, the subjects of consciousness and perception present unique challenges in the attempt to build a unifying understanding bridging between the micro-, meso-, and macro-scales of the brain and psychology. This chapter outlines an integrated view of the neurophysiological systems, psychophysical signals, and theoretical considerations related to consciousness. First, we rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 157 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…This study highlights the importance of evaluating the effects of VNS on functional connectivity, which measures the degree to which regions or networks interact with each other. It is widely recognized that brain functions emerge from coordination among regions [ 56 ]. However, prior studies address the effects of VNS in focal and target regions [ 57 ], whereas the effects of VNS on functional connectivity is perhaps more functionally relevant.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the importance of evaluating the effects of VNS on functional connectivity, which measures the degree to which regions or networks interact with each other. It is widely recognized that brain functions emerge from coordination among regions [ 56 ]. However, prior studies address the effects of VNS in focal and target regions [ 57 ], whereas the effects of VNS on functional connectivity is perhaps more functionally relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Larkum et al [19,20]suggested that the BAC firing mechanism implements coincidence detection between bottom-up sensory stream and top-down context modulation. Other studies made even stronger claims implicating bursts to be involved, via BAC firing, with conscious perception [61], visual illusions [62] and attentional modulation of activity [63]. In view of our findings of two types of bursts, these effects could be reexamined, and the impact of dendritic inhibition of L5 pyramidal neurons on such high-level processing explored.…”
Section: Implications Of Burst Control On Perceptionmentioning
confidence: 58%
“…Larkum et al (2009; 2013) suggested that the BAC firing mechanism implements coincidence detection between bottom-up sensory stream and top-down context modulation. Other studies made even stronger claims implicating bursts to be involved, via BAC firing, with conscious perception (Anastassiou and Shai 2016), visual illusions (Bachmann 2015) and attentional modulation of activity (Anderson, Mitchell, and Reynolds 2011). In view of our findings of two types of bursts, these effects could be reexamined, and the impact of dendritic inhibition of L5 pyramidal neurons on such high- level processing explored.…”
Section: Discussionmentioning
confidence: 99%